Effects of whole grain and distillers dried grains with solubles from normal and heterowaxy endosperm sorghums on growth performance, nutrient digestibility, and carcass characteristics of finishing pigs - Senne, B.W.; Hines, Robert H.; Dean, D.W.; Mavromichalis, I.; Froetschner, J.R.; Hancock, Joe D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
No differences occurred in ADG, ADFI, F/G, digestibilities of DM and GE, dressing percentage, 10th rib fat depth, or fat free lean index in pigs fed normal vs heterowaxy sorghums. As anticipated, with the greater fiber and lower energy in distillers dried grains with solubles (DDGS) than the parent cereal grains, ADG and digestibilities of DM and GE were lower and F/G was worse for pigs fed DDGS. However, the energy value of the DDGS was affected less adversely when heterowaxy sorghum was used for fermentation to ethanol.
Keywords: Swine; Sorghum; Distillers grains; Waxy; Endosperm; Finishing pigs